(3GdCSGdjH GdcejI aj GdJShjb (B/s - (3GdaVd, eDjO YHO GdMSjfs; (3Ydj YHO GdQVG GdLjGTjs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2004)
(3eaGgje YGeI aj GdJShjb hGdCSGdjH GdcejI hGdJWQb Gdi GdGSGdjH GdcejI aj GdJSYjQ eY JfGhd GdJfHD HGdeHjYGJ h JMOjO GdMUI GdShbjI ddefTCI ,h GdCSGdjH GdcejI aj GdJhRjY h JMdjd GdbQGQGJ GdJShjbjI h OQGSJgG hab fXQjI dbQGQ eY JfGhd GdCSGdjH GdcejI aj GdJQhjL h GdgjefI Ydi GdShb h cPG JShjb GdSdY h GdNOeGJ HGYJeGO GSdhH NWhW GdGfJXGQ h GdJWQb Gdi GdefgL Gdcej aj OQGSI Sdhc GdeSJgdc h CNjQG ESJNOGe GdHQeLI GdNWjI aj eYGdLI GdeTGcd(B.s
Keywords: (3GdCSGdjH GdcejIs; (3GdJShjbs